Evaluating Feigned Psychiatric Symptoms in Forensic Psychiatry: Case Series and Clinical Indicators - Supriya; Chahal, Savita; Sharma, Jai; Aggarwal, Ashish; Pandey, Arun Kumar (Jurnal Psikiatri Surabaya, 2026)
Introduction: Malingering, the intentional fabrication or exaggeration of symptoms for external gain, remains a significant challenge in forensic psychiatry. Psychiatric illnesses are particularly vulnerable to malingering due to their subjective symptom profiles and absence of objective biological markers. Early recognition is critical to protect genuine patients and maintain judicial integrity. Methods: We report three medico-legal cases referred by judicial authorities for psychiatric evaluation of fitness to stand trial. Each case was assessed through a multidisciplinary approach involving repeated clinical interviews, behavioral observation, review of medical records, collateral history, and standardized psychological assessments, including the Rorschach test and the Minnesota Multiphasic Personality Inventory (MMPI). Results: Indicators of malingering included initiation of treatment only after legal proceedings, inconsistencies between reported symptoms and observed behavior, and absence of expected side effects despite high-dose antipsychotics. Case I showed Ganser-like responses with intact Rorschach findings. Case II had elevated MMPI validity scales (F, Fp, FBS), consistent with over-reporting. Case III refused testing and displayed contradictions, such as claiming hallucinations without observable distraction. Together, these findings supported malingering driven by legal avoidance. Discussion: This series underscores the importance of multimodal evaluation in detecting malingering. Findings support The findings support the importance of multidisciplinary collaboration and the use of structured tools to improve diagnostic accuracy, prevent misuse of psychiatric diagnoses, and ensure justice in medico-legal contexts.